Konflik Sosial Dalam Novel Zuhur Ta’kuluha Al-Nar Karya Amir Taj El-Sir (Kajian Sosiologi Sastra) - Fadhila Nurul ’Izza, Izza; Dayudin; Ade Ahmad Suprianto (Pupujian, 2024)
This research is motivated by problems that arise in the novel Zuhur Ta’kuluha Al-Nar by Amir Taj El-Sir. Literary work is art that is expressed using language. Creating literary works cannot be separated from the conditions of the surrounding environment. It is not uncommon for authors to create literary works indirectly to describe the existing reality. Such as social inequality, crime, social conflicts that exist in society. One of the novels that raises various issues such as politics, social inequality, injustice and crime is the novel Zuhur Ta’kuluha Al-Nar by Amir Taj El-Sir. This research uses Soejono Soekanto’s theory regarding Sociology. This research aims to (1). Know the intrinsic elements contained in the novel Zuhur Ta’kuluha Al-Nar by Amir Taj El-Sir. (2). Understand the social conflict contained in the novel Zuhur Ta’kuluha Al-Nar by Amir Taj El-Sir. The method used in this research is a qualitative descriptive analytical method using a Literary Sociology approach. The results of this research are (1). Intrinsic elements contained in the novel Zuhur Ta’kuluha Al-Nar by Amir Taj El-Sir. (2). The social conflicts found were: a). Personal social conflict. b). Social conflict. c). Sociopolitical conflict. d). socio-cultural conflict. This is proven by the data found on 22 social conflict data. Keywords: Social Conflict, Amir Taj El-Sir, Sociology of Literature.